Manhaj Al-Quran in Maintaining the Sanctity of the Islamic Faith - Haswira Salleh Ahim (MAQOLAT: Journal of Islamic Studies, 2026)
In the contemporary context, the purity of the Islamic creed faces various intellectual and ideological challenges, such as secularism, liberalism, and other deviant currents, alongside the influence of digital media that normalizes values contrary to Islamic teachings. This situation necessitates a clear and authoritative framework to safeguard the integrity of the Muslim creed. Accordingly, this study aims to analyze the core principles of the Qur’anic methodology in preserving the creed, particularly through the affirmation of tawḥīd, the rejection of shirk, and the rectification of doctrinal deviations. The study employs a library research method with a qualitative, text-based analytical approach, involving content analysis of Qur’anic verses and the interpretations of authoritative scholars in the fields of creed and Islamic thought. The findings indicate that the Qur’an presents a comprehensive and integrated methodology for preserving the creed, encompassing the construction of faith grounded in tawḥīd, the purification of belief from elements of shirk and superstition, and the exposure of various forms of misguidance and intellectual deviation. This methodology functions not only as a defensive safeguard for the creed but also as an effective and relevant framework for faith education in addressing contemporary challenges faced by the Muslim community.